Peningkatan Keaktifan dan Hasil Belajar IPA Melalui Penggunaan Strategi Teams Games Tournament pada Siswa Kelas III SD Negeri Rejosari 3 Tahun Ajaran 2015/2016 - Lestari, Riski Nurdian; , Dra. Risminawati, M.Pd (2016)
Learning Natural Science makes teachers must be able to urge students' curiousity and motivate them, so students can be more active in learning. If students are active in learning, then there will be interaction between students and teacher. Therefore, the learning can be useful (meaningful) for students. The purpose of this research is increasing the students' regularity in learning Natural Scinece by usingTeams Games Tournament strategy and the students' scores of Natural Science throughTeams Games Tournament strategy of third grade students of SD Negeri 03 Rejosari (State Elementary of Rejosari 3) year 2015/2016. This researh mrthod is Classroom Action Researh (CAR). The method of collecting data used are; 1) interview, 2) observation, 3) documentation, and 4) test. The results shows that Team Games Tournament strategy can increase the students' regularity and students' score of learning Natural Science. It is proven by the average procentage of students' regularity, i.e. pra cycle is 48,89%, cycle 1 of the first meeting is 53,49% and second meeting is 63,97%, and cycle II of first meeting is 66,87% and second meeting is 84,19%. The students' average score of Natural Science of pra cycle is 67,64, cycle I is 71,44, and cycle II is 80,08. Based on the result of class behavioral research that has been done in two cycles, it can be concluded that the students' regularity are increased in learning Natural Science throughTeam Games Tournament strategy.